The sphinx of time: where is socialism going? - Oliveira, Francisco de (1981)
In this conference, the author aims to analyze important aspects on the state ofthe socialist economy. It deals with the concept of socialism itself as a transitory phase, therole of bureaucracy and the terms of the revolution. JEL Classification: P20, P30, B51.